ANALISIS UNJUK KERJA KOMPUTASI DISTRIBUTED SHARED MEMORY PADA SISTEM CLUSTER KOMPUTER PERSONAL - Gozali, Ferrianto; Lagusto, Dimas (Jurnal Teknik Elektro, 2005)
Parallel processing systems that support the shared memory abstraction are becomingwidely accepted in many areas of computing. The shared memory or single system image ofaddress space abstraction provides several advantages over the message passingabstraction. Distributed shared memory or DSM is a memory configuration system that canbe used to provide a coherent shared address space for a workstation clusters or looselycoupled systems which have no support for shared memory in hardware.The purpose of thispaper is to describe issues related to the implementation of DSM in Personal ComputerCluster system. The system is developed under Linux operating system and clustermiddleware Parallel Virtual Machine [PVM]. In this research, an object-based DistributedShared Memory (DSM) system called Adsmith is used on the top of PVM. An applicationprogram for A Traveling Salesman Problem (TSP) is tested using different scenarios to getaverage execution time and speedup of the computation. Each scenario represents a differentnumber of node cluster involved for computation. The results show that programs developedwith Adsmith can achieve better performance comparable to that developed with PVM inhigh computation environment.Keywords: Distributed Shared Memory, komputer cluster, Parallel Virtual Machine,Adsmith.